Aquela belicosa raynha com valor costumaz : as ambiguidades de Ginga na obra história geral das guerras angolanas de Oliveira de Cadornega e seus usos na historiografia brasileira - Weber, Priscila Maria (2014)
The present research aims to analyze the descriptions related to african queen Ginga in the book "História Geral da Guerras Angolanas", writen in Luanda in the year 1681 by the portuguese soldier António de Oliveira de Cadornega. To do so, we contextualize the writing of the work noting how the author embarks towards Africa, his stabilization with raised titles and positions in the forty years he stayed in Angola, which resulted the motes that generated the work. After this step, were observed ambiguities in the text of Oliveira de Cadornega regarding the Ginga character, like adjectives that characterize the queen, sometimes semantically indeterminate, or the use of dialogies between Kimbundo and Portuguese languages. Orchestrating these elements give meaning to such work, support the author's goals or his stay in Africa. The last chapter of this analytical work is a historiographical debate, which observes the work HGGA as a documentary source. Thus, we question the use of the adjectives that characterize the Queen Ginga from the work of Cadornega in studies of Brazilian historiography.